Characterization of selected organometallic compounds by electrospray ionization‐ and matrix‐assisted laser desorption/ionization‐mass spectrometry using different types of instruments: Possibilities and limitations. (21st March 2022) - Fleissner, Sarah; Pittenauer, Ernst; Pecak, Jan; Kirchner, Karl
Abstract : Rationale: Organometallic compounds are becoming increasingly important in their industrial application as catalysts. Mass spectrometry is an essential tool for the structural confirmation of such organometallics. Because the analysis of this class of molecules can be challenging, the ionization behavior and structural confirmation of selected transition metal catalysts are described in this work. Methods: The transition metal catalysts investigated were analyzed using classical vacuum MALDI reflectron TOF‐MS as well as intermediate pressure matrix‐assisted laser desorption/ionization quadrupole time‐of‐flight mass spectrometry (MALDI QTOF‐MS). Obtained mass spectra were compared with electrospray ionization MS (ESI‐MS) already established for organometallic compounds, utilizing a QTOF mass spectrometer here. In addition, various sample preparations, including two selected MALDI matrices ( trans ‐2‐[3‐(4‐ tert ‐butylphenyl)‐2‐methyl‐2‐propenylidene]malononitrile and 2, 2′:5′, 2″‐terthiophene) with different solvent combinations for MALDI‐MS measurements, were investigated in detail with respect to their correct isotope distribution of the molecular ions observed. Results: All investigated organometallic compounds were successfully identified by vacuum and intermediate pressure MALDI‐MS. Accurate masses of ions related to molecular ion species (e.g., [M‐Cl] +, [M] +, and [M + Na] + ) could be determined by MALDI QTOF‐MS measurements with a mass error of less than ±5 ppm for all compounds. Both investigated MALDI matrices performed equally on both instruments. The impact of the analyte/matrix solvent mixtures turned out to be crucial for a successful analysis of the investigated compounds. In contrast, ESI QTOF‐MS yielded masses of ions related to molecular ion species in favorable cases. Conclusions: The use of MALDI‐MS for the structural confirmation of organometallic compounds is still not widely used. Nevertheless, this work showed that this analytical technique does have some benefits. The analysis of neutral catalysts proves to be quite useful, concluding that this technique provides a complement and/or an alternative to ESI‐MS.